Peran Tim Nurul Musthofa dalam Mempromosikan Produk Seni Islam dan Kontribusinya terhadap Ekonomi Umat - Baharudin Ardani; Muhamad Zen; Fatmawati Fatmawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the role of Tim Hadrah Nurul Musthofa in promoting Islamic art products and its contribution to strengthening the community’s economy through a literature review approach. As a religious art group, Tim Hadrah not only serves as a medium for da’wah and the preservation of Islamic culture, but also holds potential as a community-based creative economic agent. This research employs a literature study method by analyzing various written sources such as books, scientific articles, media documentation, and relevant digital content. The findings indicate that Tim Hadrah Nurul Musthofa is actively engaged in producing and marketing Islamic art products through social media platforms, live performances, and merchandise sales. These activities contribute to local economic empowerment and open up opportunities for synergy between art, da’wah, and the Muslim economy. This study underscores the importance of developing culturally grounded da’wah through Islamic arts as a means of social and economic empowerment in modern society.